Posttranslational modifications of lysine and evolving role in heart pathologies-recent developments - Stastna, Miroslava; Van Eyk, Jennifer E (Proteomics, 2015)
The alteration in proteome composition induced by environmental changes and various pathologies is accompanied by the modifications of proteins by specific cotranslational and PTMs. The type and site stoichiometry of PTMs can affect protein functions, alter cell signaling, and can have acute and chronic effects. The particular interest is drawn to those amino acid residues that can undergo several different PTMs. We hypothesize that these selected amino acid residues are biologically rare and act within the cell as molecular switches. There are, at least, 12 various lysine modifications currently known, several of them have been shown to be competitive and they influence the ability of a particular lysine to be modified by a different PTM. In this review, we discuss the PTMs that occur on lysine, specifically neddylation and sumoylation, and the proteomic approaches that can be applied for the identification and quantification of these PTMs. Of interest are the emerging roles for these modifications in heart disease and what can be inferred from work in other cell types and organs.
Keywords: lysin; myši; kardiomyocyty; skot; krysa rodu Rattus; Sumoylation; Humans; Cells, Cultured; Heart pathologies; Proteome; lidé; myokard; Molecular Sequence Data; Rats; Technology; proteom; Lysine PTMs; sekvence aminokyselin; Animals; Myocardium; Modified proteins; Mice; zvířata; Heart Diseases; nemoci srdce; molekulární sekvence - údaje; Lysine; kultivované buňky; Cattle; posttranslační úpravy proteinů; Protein Processing, Post-Translational; Myocytes, Cardiac; Neddylation; Amino Acid Sequence